(3TQM fgL GdHdGZIs - (3CHh MGeO, GHf CHj GdMOjO, YR GdOjf, YHO GdMejO Hf gHI Gddg Hf eMeO Hf GdMSjf Hf CHj GdMOjO, (B656 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3GdCUd hef cdGe dg Ydjg GdSdGe hbO hbYJ Hjfg hHjf YKeGf eTGLQI abGd GdeZjQI (B..(3dYKeGf (B: (3CfG Ccajcg , abGd CejQ GdeDefjf Ydjg GdSdHGe ddeZjQI (B...s
(3BNQgG (B:s
.. (3Efg CUM GdfGS JOHQG hCMSfge SjGSI hEfeG Gdghi hGdYUHjI dG MjdI ajgeG , GdCUd hef cdGe dg Ydjg GdSdGe CjgG GdfGS dG JSJhMThG aj WQjb GdgOi dbdI Cgdg aEf GdfGS (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\289s
(3cTa GdXfhf (B2\1991s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs